Wideband circularly polarized fractal antenna with SSRR metasurface for 5G applications - Al-Abbasi, Maalim; Abdul Latef, Tarik (International Journal of Electrical and Computer Engineering Systems, 2024)
In this study, a 3.5 GHz wideband circularly polarised antenna design is presented. The suggested antenna is constructed using square and flower fractal shapes within the patch. The square fractal shapes and flower fractals are implemented inside the slot patch and in the top left and right corners of the patch. The key advantage of using this method is to increase the bandwidth of the antenna besides reduce the size and improve the axial ratio. Then a Square Split Ring Resonator (SSRR) metasurface is added above the antenna for enhancement of gain and back lobe. The metasurface is added on the front of the antenna in order to increase the gain directivity and decrease the sidelobes and back lobe. Using computer simulation software (CST), the proposed metasurface antenna is simulated and then constructed on FR4 substrate with dimensions of (ε_r=4.4 and h=1.6 mm). Operating bandwidth between 1.79 GHz and 5 GHz is achieved, the metasurface antenna's performance attained a fractional bandwidth of 91%. An improved gain of 3.05 dB is observed when metasurface is applied. A measured AR below 3 dB is achieved over the obtained bandwidth. The proposed fractal was reduced in size by 40.43% as compared to conventional antennas. The antenna recommended is suitable for use in the fifth generation (5G) applications.